Reanalysis of two studies with contrasting results on the association between statin use and fracture risk: the General Practice Research Database. - de Vries, F; de Vries, C; Cooper, C; Leufkens, B; van Staa, T (2006)
BACKGROUND: Two recent case-control studies by Meier et al. and van Staa et al. used the UK General Practice Research Database (GPRD) to examine the association between the use of statins and the risk of fractures, with different results. The objective of the present study was to examine methodological explanations for the discrepant results. METHODS: We created two datasets, which mimicked the previous study designs: a 'selected population' (SP) case-control dataset, with fracture cases matched to controls nested within a selected cohort (Meier et al.), and an 'entire population' (EP) case-control dataset, with both cases and controls sampled from the total GPRD population (van Staa et al.). Cases and controls were matched by gender, age (year of birth or 5 year age bands), and general practice. RESULTS: The study included 131 855 fracture cases. The crude odds ratio (OR) for hip fracture in statin users was 0.37 (95% CI 0.27-0.52) in the SP and 0.54 (95% CI 0.39-0.74) in the EP dataset. This difference was reduced when matching by year of birth, rather than by 5 year age bands: crude ORs were 0.58 (95% CI 0.43-0.79) and 0.61 (95% CI 0.44-0.88), respectively. In the SP dataset, 37% of the cases could be matched by year of birth, while this was achieved for 99% in the 'EP' dataset. The exposure time-window, the selection of confounders, and exclusion of high-risk patients also influenced results. CONCLUSION: Residual confounding by a matching variable and different definitions of the exposure time window explained differences in results. In case-control studies of drug use and fracture risk, broad matching criteria for age should be avoided and the selection of the time-window for exposure should be carefully considered.